Returns to education of Colombian care workers before and after the COVID 19 pandemic - Rodríguez, Dustin Tahisin Gómez; Perez, Ehyder Mario Barbosa (Edelweiss Applied Science and Technology, 2025)
This article aims to examine how human capital is reflected in the field of care work in Colombia, emphasizing its relevance for the sustainable progress of the country, both before and after the COVID-19 pandemic. A quantitative methodology was employed, conducting a microeconometric model through Mincerian equations with data from the Integrated Household Survey (GEIH) provided by the National Administrative Department of Statistics (DANE) for the periods 2018, 2019, 2021, and 2022. The main conclusion highlights the intrinsic relationship between human capital, care jobs, and the Colombian reality, underscoring the complexity and multidimensionality of these aspects. While investment in skill and knowledge development is crucial for the country’s advancement, the lack of visibility and recognition of care jobs, despite their critical impact on society, poses a significant challenge.